Analisis Faktor Psikologi Yang Mempengaruhi Stress Kerja Pada PT. XYZ - Mukti, Anggoro Daru; Praditar, Bayu Surya; Setiyawan, Andie (JURNAL TEKNIK INDUSTRI, 2022)
Uncomfortable workplace conditions play an important role in causing work stress. Whereas work stress can directly affect the safety and health of workers. This is because work stress can trigger health problems and even work accidents. The method used is a quantitative method. The data obtained from the results of distributing questionnaires with a total of 250 respondents were processed and analyzed using SPSS 22.00 software for windows. Factor 1 was able to explain 37.461% of variations, namely role ambiguity, role conflict, career development, work stress, work conflict. While factor 2 explains 20.126% of the variation which includes quantitative overload, qualitative overload. From these results, to reduce employee work stress, it is necessary to make clear SOPs for each employee and make team building sessions between leaders and employees in reducing the workload.